Analysis of activation and dissipation energies in Jeffery-Hamel flow (JHF) through non-parallel stretchable channels - Ikram Ullah; Subhan Ullah; Marouan Kouki; Hamda Khan; Zareen A. Khan (Results in Engineering)
This research article investigate the dynamics of fluid flow in non-parallel stretchable walls which focusing on the Jeffery-Hamel (JH) flow. This study analyzed activation and dissipation energies, investigating how these factors interact in the framework of differential type fluid flow. The findings provide insights into the behavior of fluid in complex geometries, with potential applications in microfluidics, biomechanics, and industrial processes. The main equations are non-dimensionalized through valid parameters and used NDSolve software numerically. Magnetic field increases as well as skin friction and Nusselt also increases.